Knocking out central metabolism genes to identify new targets and alternating substrates to improve lipid synthesis in Y. lipolytica - Zhu, Jiang; Gu, Yang; Yan, Yijing; Ma, Jingbo; Sun, Xiaoman; Xu, Peng (Frontiers in Bioengineering and Biotechnology, 2023)
Systematic gene knockout studies may offer us novel insights on cell metabolism and physiology. In the oleaginous yeast Y. lipolytica, the lipid accumulation mechanism at the molecular or cellular level is yet to be determined. In this work, we established 12 engineered strains with the knockout of important genes involving in central carbon metabolism, NADPH generation, and fatty acid biosynthetic and degradation pathways. We demonstrated that NADPH sources for lipogenesis include the OxPP pathway, POM cycle, and isocitrate-2-oxoglutarate shuttle, despite that OxPP pathway is the primary NADPH source for lipogenesis. Specifically, we found that the knockout of mitochondrial isocitrate dehydrogenase IDH2 could facilitate fatty acid synthesis and acetate is a more favorable carbon source for fatty acids synthesis when glycolysis step is impaired, indicating the evolutionary robustness of Y. lipolytica in response to alternate carbon sources. To our knowledge, this is the first report on enhancing lipid titers by deleting central metabolism genes when an alternate carbon source (acetate) was used. This systematic investigation of gene deletions across various lipogenic pathways would help us better understand lipogenesis and engineer yeast factories to upgrade the lipid biomanufacturing platform.